Technologies for the benefit development of low-permeability tight sandstone gas reservoirs in the Yan'an Gas Field, Ordos Basin - Xiangzeng Wang; Xiangyang Qiao; Naizhe Mi; Ruogu Wang (Natural Gas Industry B, 2019)
The Yan'an Gas Field is located in the southeastern part of the Ordos Basin, and its low-permeability tight sandstone gas reservoirs are characterized by thin reservoirs, poor physical properties and complex overlapping relationships. In addition, its surface is loess tableland, which makes it difficult to predict reservoirs by using seismic data. As a result, existing engineering technologies for gas field development cannot support the efficient development of this field. In order to optimize the development methods and technologies of the Yan'an Gas Field, the Yanchang Petroleum (Group) Co. Ltd. has developed to a set of key technologies suitable for the benefit development of this field concerning reservoir prediction, well pattern optimization, drilling and completion, reservoir protection, fracturing stimulation and ground gathering and transportation after nearly ten years of theoretical and technical researches. First, an effective reservoir prediction technology based on dynamic knowledge base was developed. It improves the drilling ratio of effective sandbody dramatically and achieves the accurate tracking of stable single sandbody in the range of 3–5 m. Second, a three-dimensional exploitation mode of hybrid well pattern based on the irregular diamond-shaped well pattern was established. It includes the multi-layer commingled production of cluster well and the single-layer production of horizontal well. Compared with regular well patterns, the well number is reduced by 6.9% and well pattern control is increased by 8%. Third, high-efficiency drilling technology for vulnerable reservoirs with collapse and leakage in the same well was developed. It improves wellbore wall stability, shortens drilling cycle and protects reservoir. Fourth, the multi-layer long-span fracturing of vertical/directional wells in one operation and the CO2 and hydraulic fracturing treatment of horizontal wells were realized to improve single well production significantly. Fifth, the medium-pressure gathering and transportation system in loess tableland with downhole throttling, branch-on-branch inter-well tandem and centralized alcohol injection as the core technologies was established. It reduces workload, shortens construction cycle and improves economic benefit. In conclusion, these development technologies play a crucial role in the development, appraisal and productivity construction of the Yan'an Gas Field. Through the application of these key technologies, the benefit development of this field is realized with an annual natural gas production capacity of 50 × 108 m3. Furthermore, they are conducive to the enrichment and development of the theories and technologies for developing tight sandstone gas reservoirs in China, and they can be used as a reference for the development of similar gas fields. Keywords: Ordos Basin, Yan'an Gas Field, Tight sandstone gas reservoir, Reservoir, Prediction, Hybrid well pattern, Low-damage fracturing, Benefit development